Fabrication of biaxially textured Ni substrates and LaNiO3 buffer layers for Tl-1223 thick films - Gladstone, T; Moore, J; Wilkinson, A; Grovenor, C (1999)
We have fabricated cube texture nickel substrates and examined the relationship between percentage rolling deformation and annealing conditions on the degree of texture obtained using,XRD and EBSD techniques. We have found that unaligned grains may be avoided by rolling to 95% reduction and annealing at 800 degrees C for 4 hours. We have fabricated LaNiO3 films on YSZ and lanthanum aluminate by spray pyrolysis and achieved cube texture in thin coatings.